Development and in vitro characterization of self-emulsifying drug delivery system (SEDDS) for oral opioid peptide delivery. (3rd October 2017) - Zupančič, Ožbej; Rohrer, Julia; Thanh Lam, Hung; Grießinger, Julia Anita; Bernkop-Schnürch, Andreas
Abstract: Aim: In this study, self-emulsifying drug delivery system (SEDDS) for oral delivery of opioid peptide dalargin were developed and characterized in vitro . Methods: Dalargin lipophilicity was increased by O-esterification of tyrosine OH group, hydrophobic ion pairing, or a combination thereof. Distribution coefficients (log  D ) of lipidized dalargin derivatives were determined. Then, dalargin was incorporated in chosen SEDDS, namely SEDDS-1, composed of 50% Capmul 907, 40% Cremophor EL, and 10% propylene glycol and comparatively more lipophilic SEDDS-2 composed of 30% Captex 8000, 30% Capmul MCM, 30% Cremophor EL, and 10% propylene glycol. Additionally, SEDDS were characterized regarding droplet size, polydispersity index (PDI), cloudy point, physical stability and stability against pancreatic lipase. Furthermore, mucus permeating properties of SEDDS and their ability to protect the incorporated dalargin against proteolysis by trypsin, α-chymotrypsin, elastase, simulated gastric fluid (SGF), and simulated intestinal fluid (SIF) were evaluated. Results: The highest dalargin drug payload of 4.57% in SEDDS-2 was achieved when dalargin palmitate (pDAL) was ion paired with sodium dodecyl sulfate (SDS) in molar ratio 1:1. Moreover, SEDDS-1 and SEDDS-2 had a narrow droplet size distribution with average droplet sizes of 42.1 and 33.1 nm with PDI of 0.042 and 0.034, respectively. Lipolysis study showed that within 30 min 78.5% of SEDDS-1 and 92.1% of SEDDS-2 were digested. In addition, both SEDDS exhibited mucus permeating properties as well as a protective effect against enzymatic degradation by trypsin, α-chymotrypsin, elastase, SGF and SIF. Conclusion: The results of this study suggest that the developed SEDDS could be considered for oral opioid peptide delivery.